Mining lifecycles in Mongolia and Kyrgyzstan - Sternberg; Toktomushev; Ichinkhorloo (2021)
The lifecycle of a mine brings opportunities and challenges to host societies and communities. In Mongolia and Kyrgyzstan, mining presents political, social, environmental and cultural contexts that place extraction at the centre of national debates. These two ex-Soviet states share similar 20th-century history, pastoralism, steppe traditions and now democratic approaches to governance. As mineral-rich countries on China’s frontier mining processes have affected economics, communities and political engagement. Here we situate Mongolia and Kyrgyzstan within post-Soviet, country and international contexts that are key to understanding contemporary challenges. Today political contestation, China’s Belt and Road Initiative and environmental degradation affect mining viability and outcomes. How mining regimes developed, perceived costs and benefits and citizen and community engagement frame national development. Whilst the process of mine exploration, extraction and closure reflect regional dynamics, the resource extraction experience in Kyrgyzstan and Mongolia is shared across developing countries